Effect of different lighting programs during egg incubation on some productivity indicators and sexual maturity of the Japanese Quail (Coturnix Japonica) (Journal of Hama University, 2022)
The purpose of this research was to study the effect of different lighting programs during the incubation period, on the sexual maturity and productive performance of the hatched chicks using LED light. A total of  288 one day old Japanese quail chicks were used in the experiment, and the chicks were divided into three equal treatments, with 96 chicks for each according to the lighting program applied to them during the incubation period: T1 (continuous darkness (0L:24D) (control)), T2 (12 hours light versus 12 hours darkness (12L:12D)) and T3 Continuous Light (24L: 0D)), Each treatment was divided into three replicates, with 32 chicks for each, at the same shelter, care and nutrition conditions for all treatments.The results showed that treatment T2 was significantly (P≤0.05) superior to the final mean live weight at 6 weeks of age, and the total feed conversion (214.88 g, 2.67), when compared to the other two treatments T1 (201.02 g, 2.82) and T3 (186.22 g, 3.06), respectively.The results showed a delay in reaching sexual maturity for males and females in the treatment T3, as this period was (35.78, 46.13) days, compared to the males and females of the two treatments T2 (34.44, 44.45) days, and T1 (35.06, 44.90) days respectively, The mean live weight at sexual maturity of males and females treatment T2 (188.88, 235.89)g was significantly higher (P≤0.05) than the other two treatments T1 (179.43, 222.87)g and T3 (163.24, 206.91)g, respectively, The results also indicated that there were no significant differences in mortality rate, average feed consumption, and egg production characteristics (percentage of egg production, the number of cumulative eggs, weight of eggs, the mass of eggs) in comparison between the studied treatments and the control treatment, These results showed the importance of applying an LED lighting program for 12 hours light and 12 hours darkness during the incubation period, and its role in improving the productive and reproductive indicators of the hatched chicks.